Degradation study of InGaN-based laser diodes grown on Si. (9th July 2020) - Tang, Yongjun; Feng, Meixin; Wen, Pengyan; Liu, Jianxun; Wang, Jin; Sun, Xiujian; Sun, Qian; Zhang, Shuming; Sheng, Xing; Ikeda, Masao; Yang, Hui
Abstract: The degradation characteristics of InGaN-based laser diodes (LDs) grown on Si substrate have been studied under an electrical stress with a pulsed current of 180 mA. After the electrical stress, the light output power, leakage current and capacitance of the LD decreased, while the operation voltage and threshold current increased, and the slope efficiency remained nearly unchanged after the pulsed electrical stress for 620 h. Further analysis shows that the degradation was probably due to the newly generated group-III vacancies and/or related defects, which can not only act as acceptor-like defects to compensate the n-type donors, leading to the reduction of conductance and capacitance, but also work as non-radiative recombination centers affecting the internal quantum efficiency and emission intensity of the active region.